Poultry Litter Affects Forage Dry Matter Yield and Total N and P Uptake - Sidat Yaffa,; Sidat Yaffa, (Global Journal of Human-Social Science, 2014)
Forage crops play an important role in removing P and N from poultry litter-amended soils there byminimizing environmental pollution A three year study was conducted at Crossville AL to compare dry matter yield and total P and N removal efficiencies by forage crops from a poultry litter-amended soil Forage crops including alfalfa Medicago sativa L rye Secalecereale L corn Zea mays L sorghum-sudangrass Sorghum bicolor L cv Unigraze II tall fescue Festucaarundinacea L cv KY31 and Russell bermudagrass Cynodondactylon L were investigated The soil type at the site was a Hartsells fine sandy loam fine-loamy siliceous thermic TypicHapludults The highest dry matter yield in 2001 was observed with sorghum-sudangrass and in 2002 and 2003 it was observed with Russell bermudagrass respectively In 2001 the lowest dry matter yield was observed with alfalfa in 2002 it was observed with corn and in 2003 it was observed with sorghum-sudangrass alfalfa and Russell bermudagrass respectively Sorghum-sudangrass showed the highest N uptake in 2001 alfalfa and Russell bermudagrass showed the highest N uptake in 2002 and 2003 respectively Tall fescue showed the highest P uptake in the three-year study Russell bermudagrass appears to be the most effective forage crop for removal of N and tall fescue for the removal of P from soils amended with poultry litter